1972
DOI: 10.1302/0301-620x.54b4.648
|View full text |Cite
|
Sign up to set email alerts
|

Progressive and Resolving Infantile Idiopathic Scoliosis

Abstract: The radiograph at 5 months of a typical resolving curve, initially 33 degrees with an angle difference of 16 degrees. The rib head on the convex side is clear of the body of the apical vertebra (Mehta's Phase 1) (left-hand side). The radiograph eighteen months later showing normal appearances (right-hand side).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 0 publications
2
8
0
1
Order By: Relevance
“…This observation was confirmed in later studies [5,8,16], and it was further reported that the RVAD is of prognostic importance in juvenile scoliosis as well [17]. Measurements of RVAs have been used in analyses of the effect of various surgical procedures on the rib cage in patients with IS [26], RVA values have also been used in studies of the shape of the thorax during growth [11,27] and it has been suggested that asymmetries between the left and right RVAs result from an imbalance between ;muscular forces on either side of the spine and that this could be an important factor in the pathogenesis of adolescent IS [3].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…This observation was confirmed in later studies [5,8,16], and it was further reported that the RVAD is of prognostic importance in juvenile scoliosis as well [17]. Measurements of RVAs have been used in analyses of the effect of various surgical procedures on the rib cage in patients with IS [26], RVA values have also been used in studies of the shape of the thorax during growth [11,27] and it has been suggested that asymmetries between the left and right RVAs result from an imbalance between ;muscular forces on either side of the spine and that this could be an important factor in the pathogenesis of adolescent IS [3].…”
Section: Introductionsupporting
confidence: 70%
“…In this context it must be pointed out that measurements of the RVADs in some earlier studies have concentrated on the level of the apical vertebra [5,8,16,18,24] where the difference, as seen in the present study, is the least. Earlier conclusions regarding the importance of the RVAD at the apical level could therefore change if this is taken into consideration.…”
Section: Discussionmentioning
confidence: 52%
“…Although the prognosis of the infantile asymmetry complex is thought to be good in most cases, retrospective studies have shown persistent or progressive scoliosis in 10-50% of all patients (Lloyds-Roberts and Pilcher 1965, Ferreira et al 1972, James 1975, Wynne-Davies 1975, Thompson 1980, Canale et al 1982, McMaster 1983, Binder et al 1987. A recent 2-year prospective study showed that in 25% of asymmetric infants asymmetric features will persist (Boere-Boonekamp and van der Linden-Kuiper 2001).…”
mentioning
confidence: 99%
“…Some curves progress and cause cardiopulmonary pathology [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] while others resolve or disappear spontaneously within the first years of life. 4,7,12,[18][19][20][21] In 1951, James 1 described this separate resolving type of infantile scoliosis. Two theories have been proposed to explain its cause, intrauterine moulding and postnatal external pressure on the spine.…”
mentioning
confidence: 99%
“…As yet, only short-and medium-term or minor long-term observations concerning resolving infantile scoliosis are available. 2,[5][6][7]9,10,12,17,19,21,30,31 In contrast to progressive infantile, juvenile and adolescent idiopathic scoliosis, little is known about its natural history at and beyond skeletal maturity. While there are guidelines concerning the treatment of progressive idiopathic scoliosis which have been verified in many clinical studies, there is not a standardised concept for the management of resolving idiopathic scoliosis.…”
mentioning
confidence: 99%